Direct evidence of enhanced chlorine segregation at grain boundaries in polycrystalline CdTe thin films via three‐dimensional TOF‐SIMS imaging. (25th April 2014) - Harvey, Steven P.; Teeter, Glenn; Moutinho, Helio; Al‐Jassim, Mowafak M.
Abstract For more than 25 years, the CdTe photovoltaic research and manufacturing communities have been subjecting CdTe materials to a CdCl2 treatment or activation step to improve performance. However, little work has been carried out using imaging to elucidate the spatial distribution of chlorine in the CdTe devices after this treatment. This work addresses fundamental questions about the spatial distribution of chlorine in the CdTe absorber material after a CdCl2 treatment comparable to industrial practices. We used a state‐of‐the‐art, time‐of‐flight secondary ion mass spectrometer (ION‐TOF GmbH) (Muenster, Germany) with a lateral resolution of about 80 nm to complete three‐dimensional depth‐profiling and imaging of two CdTe devices. The results clearly demonstrate enhanced chlorine concentration along grain boundaries, supporting the hypothesis that chlorine plays an important role in passivating grain boundaries in CdTe solar cells. The results are discussed in terms of possible passivation mechanisms, and the effect of chlorine on grain interiors and grain boundaries. The data are also used to estimate the free energy of segregation of chlorine to grain boundaries in CdTe. Copyright © 2014 John Wiley & Sons, Ltd.